Association between exposure to o-chlorobenzylidene malononitrile (CS riot control agent) and urinary metabolite 2-chlorohippuric acid in U.S. Army Mask Confidence Training. Issue 9 (2nd September 2017) - Buchanan, Maccon A.; Stubner, Alex; Hout, Joseph J.; Brueggemeyer, Mary; Bragg, William
ABSTRACT: This study was conducted among U.S. Army soldiers to evaluate the association between exposure to o-chlorobenzylidene malononitrile (CS riot control agent) and urinary metabolite 2-chlorohippuric acid (CHA) detected in test subjects (n = 87) after completion of Mask Confidence Training. CS exposures ranged 0.086–4.9 mg/m³ ( = 2.7 mg/m³). CHA levels (corrected for creatinine) at 2-, 8-, 24-, and 30-hr post-exposure resulted in ranges of 94.6–1120 µg/g-cr ( = 389 µg/g-cr), 15.80–1170 µg/g-cr ( = 341 µg/g-cr), 4.00–53.1 µg/g-cr ( = 19.3 µg/g-cr), and 1.99–28.4 µg/g-cr ( = 10.6 µg/g-cr), respectively. Spearman's correlation revealed CHA levels strongly correlated with time sampled (r = −0.748, p < 0.05) and weakly correlated with CS concentration (r = 0.270, p < 0.05). A linear relationship was observed between CHA, CS concentration, and time of urine sample according to the following regression equation: ln(CHA, μg/g-cr) = 5.423 + 0.316 (CS conc., mg/m³) – 0.002 (time sampled), (R = 0.910, R² = 0.827, p < 0.05). This relationship suggests that CHA has the potential to be an effective retrospective indicator of CS exposure in future biomarker developments.